Adsorption of Pb(II) from Aqueous Solution by Mussel Shell-Based Adsorbent: Preparation, Characterization, and Adsorption Performance - Wang, Quan (Materials (Basel), 2021)
As a natural biological adsorbent, shell powder is inexpensive, highly efficient, and does not leave any chemical residue; thus, it can be used to remove contaminants from water. In this study, we used mussel shells as a raw material to prepare an adsorbent. Scanning electron microscopy was used to observe the surface morphology of the mussel shell powder before and after calcination, and X-ray diffraction measurements, Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray photoelectron spectroscopy, and Brunauer–Emmett–Teller measurements were performed to analyze the structure and composition of calcined mussel shell powder. Characterization of the shell powder before and after calcination revealed a change from calcium carbonate to calcium oxide, as well as the formation of a surface porous structure. Using Pb(II) as a representative contaminant, various factors affecting the adsorption were explored, and the adsorption mechanism was analyzed. It was found that the adsorption is consistent with the Freundlich adsorption isotherm and the pseudo second-order model. The calcined mussel shell powder exhibits excellent adsorption for Pb(II), with an adsorption capacity reaching 102.04 mg/g.